A MnOx@Eu-CeOx nanorod catalyst with multiple protective effects: Strong SO2-tolerance for low temperature DeNOx processes - Yu, Chenglong; Hou, Dan; Huang, Bichun; Lu, Meijuan; Peng, Ruosi; Zhong, Zhiyong (Journal of hazardous materials, 2020)
[Display omitted] •The MnOx@Eu-CeOx catalysts were prepared by a simple chemical precipitation method.•The MnOx@Eu-CeOx catalysts presented high sulfur-poisoning resistance.•The catalyst with multiple protective effects is the key to high resistance to SO2. A novel MnOx@Eu-CeOx catalyst with multiple protective attributes was designed and fabricated using a chemical precipitation method and tested for its low temperature SCR activity. The subject MnOx@Eu-CeOx nanorod catalyst exhibited superior SCR performance and strong SO2-tolerance. The formation of the composite-shell structure enhanced the catalysts' surface acidity and redox performance, which resulted in excellent SCR performance. Moreover, the TG results suggested that the protective effect of the EuOx-CeOx composite-shell effectively reduced the deposition of the surface sulphates. The XPS, XRD analysis results of the subject catalyst together with theoretical calculations provided strong evidence that there was a strong interaction between Mn and Ce in the MnOx@Eu-CeOx. This significant interaction could provide maximum protection to the core from the effect of SO2, which also contributed to the high SO2 resistance of the catalyst. In situ FT-IR results also indicated that the chemisorbed species on MnOx@Eu-CeOx were much more stable in the presence of SO2 compared to Eu-CeOx/MnOx, which resulted in the deposition of significantly less sulphates. This low temperature SCR catalyst with multiple protective attributes, including composite shell, strong interaction and core-shell structure, is the key to long-term resistance to SO2.